PERANAN KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR KECAMATAN SAMARINDA ULU - Riyani Riyani (ADMINISTRASI PUBLIK, 2021)
Role of Head of Sub-District Leadership in Improving Employee Performance in Samarinda Ulu District Office. In accordance with the formulation of the problem, this research aims to determine how the role of the sub-district's leadership in improving employee performance in the Samarinda Ulu sub-district office, with the indicators of the role of leadership, namely Fathfinding, Aligning, Empowering and using employee performance indicators, namely quality. Work, Work Quantity, Implementation of Duties, and Responsibilities. This type of researchuses descriptive qualitative snowball sampling technique, which is a technique of determining the sample which is initially small in number, then enlarges. The results of the study show that the role of the sub-district head in improving employee performance at the Samarinda Ulu sub-district office has been running quite well in terms of work quality, work quantity, implementation of duties and responsibilities and can maximize things that are considered less than optimal in order to produce performance. which is of higher quality, because with quality performance it will have an impact on the progress of the organization itself.